Neurobiology of hypnosis and its contribution to the understanding of cognition and consciousness. - Canales Johnson, Andrés Fernando; Lanfranco, Renzo; Vargas, Esteban; Ibáñez, Agustín (Anales de Psicología / Annals of Psychology, 2012)
The growing interest for the scientific study of consciousness and the current development of neuroimaging tools have allowed to investigate the neuronal correlates of hypnosis and to expand its scope to assess normal and pathological neurocognitive phenomena. At an empirical level, theories that postulate hypnosis as a neurophysiological distinctive state of consciousness (‘state theories’), and theories that claim that hypnosis would just represent different neurophysiological changes associated to specific suggestions without no change in the state of consciousness  (‘non-state theories’); have both been assessed. In this work, these two theories are critically reviewed, their main features are discussed and their neurophysiological evidence is described. A growing body of evidence supports that a hypnotic state of consciousness involves mainly the anterior cingulated cortex and the dorsolateral frontal cortex; as well as a pattern of attenuated cortical functional connectivity. Also, we concluded that hypnotic suggestions have allowed a better comprehension of a diversity of normal and pathological neuropsychological processes. Finally, we stated that the neurophysiologic evidence until now is still insufficient to solve the debate between state and non-state theorists.